English in mind : - Puchta, Herbert (Cambridge University Press, 2004)
English in Mind is a five-level course for teenagers which combines engaging content with a strong focus on grammar and vocabulary. It takes students from beginner to upper-intermediate level and is ideal for mixed-ability classes. Example: Organised learning, imaginative content, dual entry, indevelopment learning.